Networks, hacking, and media - CITAMS@30: now and then and tomorrow - Wellman, Barry (Studies in media and communications, 2018)
Sponsored by the Communication, Information Technologies, and Media Sociology section of the American Sociological Association (CITAMS), this volume celebrates the section's thirtieth anniversary. Lead editor Barry Wellman joins forces with former and current CITAMS chairs Wenhong Chen, Shelia Cotten, and Laura Robinson, as well as Casey Brienza, founder of the Media Sociology Preconference, to look back at the history of the section, review some of its most important themes, and set the agenda for future discussion. Alongside its sister volume, The "M" in CITAMS@30: Media Sociology, this valuable book shows the impact CITAMS has had, and continues to have, on academic and public discourse. Featuring leading scholars in the fields of sociology of communication, information technologies and media, it reveals how the section had transcended disciplinary boundaries, and demonstrates how it holds the skills to address some of the biggest challenges of our digital age. It is essential reading for all those interested in both the story of CITAMS to date, and the role it will play in the future.